Recurrent atypical haemolytic uraemic syndrome post kidney transplant due to a CD46 mutation in the setting of SMARCAL1‐mediated inherited kidney disease. (February 2017) - Chan, Samuel; Mallett, Andrew J; Patel, Chirag; Francis, Ross S; Johnson, David W; Mudge, David W; Isbel, Nicole M
Abstract: Disorders in the regulation of the alternate complement pathway often result in complement‐mediated damage to the microvascular endothelium and can be associated with both glomerulonephritis and atypical haemolytic uraemic syndrome. Inherited defects in complement regulatory genes or autoantibodies against complement regulatory proteins are predictive of the severity of the disease and the risk of recurrence post kidney transplantation. Heterozygous mutations in CD46, which codes for a transmembrane cofactor glycoprotein membrane cofactor protein, usually have a lower incidence of end‐stage kidney disease and decreased risk of recurrent disease post transplant, as wild‐type membrane cofactor protein is present in the transplanted kidney. However, some patients with CD46 mutations have a second variant in other complement regulatory genes increasing the severity of disease. The following case report illustrates the course of a young adult patient with end‐stage kidney disease initially ascribed to seronegative systemic lupus erythematosus, who presented with biopsy‐proven thrombotic microangiopathy following kidney transplantation. It highlights the complexity associated with disorders of complement regulation and the need for a high index of suspicion and genetic testing in patients who present with thrombotic microangiopathy post‐transplant.